Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) 52.x = 62 + 82
=> 25 .x = 36 + 64
=> 25.x = 100
=> x = 100 : 25
=> x = 4
b) (22 + 42).x + 24 . 5x = 100
=> (4 + 16).x + 16.5x = 100
=> 20x + 80x = 100
=> 100x = 100
=> x = 100 : 100 = 1
c) 24 : x = 26
=> x = 24 : 26
=> x = 2-2 = 1/4
d) 33x + 23x = 102
=> 27x + 8x = 100
=> 35x = 100
=> x = 100 : 35
=> x = 20/7
a) 52 . x = 62 + 82
\(5^2\cdot x=36+64\)
\(5^2\cdot x=100\)
\(x=100\div5^2\)
\(x=100\div25\)
\(x=4\)
b) ( 22 + 42 ) . x + 24 . 5 . x = 102
\(\left(4+16\right)\cdot x+16\cdot5\cdot x=100\)
\(x\cdot\left(20+80\right)=100\)
\(x\cdot100=100\)
\(x=100\div100\)
\(x=1\)
c ) 24 . x = 26
\(x=2^6\div2^4\)
\(x=2^{6-4}\)
\(x=2^2\)
\(x=4\)
d) 33 . x + 23 . x = 102
\(x\cdot\left(23+27\right)=100\)
\(x\cdot50=100\)
\(x=100\div50\)
\(x=2\)
e) 78 . x = 710
\(x=7^{10}\div7^8\)
\(x=7^{10-8}\)
\(x=7^2\)
\(x=49\)
\(2^x.2^2.2^2=2^3\Rightarrow2^{x+2+2}=2^3\Rightarrow x+4=3\Rightarrow x=-1\)-1
\(\left(5^2+3^2\right).x+\left(5^2-3^2\right).x-40.x=10^2\)
\(\Rightarrow x.\left(5^2+3^2+5^2-3^2-40\right)=10^2\)
\(\Rightarrow x.\left(2.5^2-40\right)=10^2\)
\(\Rightarrow x.10=10^2\Rightarrow x=10^2:10\Rightarrow x=10\)
easy
Bài làm
a) 22.x-33=4.23+1
4.x-27=4.8+1
4.x-27=32+1
4.x-27=33
4.x =33-27
4.x =6
x =6:4
x = \(\frac{3}{2}\)
1)\(79-5\left(11-x\right)=34\)
\(\Rightarrow79-55+5x=34\)
\(\Rightarrow24+5x=34\)
\(\Rightarrow5x=-10\)
\(\Rightarrow x=-2\)
Vậy \(x=-2\)
2)\(32+2\left(7-x\right)=40\)
\(\Rightarrow32+14-2x=40\)
\(\Rightarrow46-2x=40\)
\(\Rightarrow2x=6\)
\(\Rightarrow x=3\)
Vậy \(x=3\)
3)\(\left(166-2x\right).8^9=2.8^{11}\)
\(\Rightarrow\left(83-x\right).2.8^9=2.8^{11}\)
\(\Rightarrow83-x=8^3\)
\(\Rightarrow83-x=512\)
\(\Rightarrow x=-429\)
Vậy \(x=-429\)
4)\(5^2.x-2^3.x=51\)
\(\Rightarrow x\left(5^2-2^3\right)=51\)
\(\Rightarrow x\left(25-8\right)=51\)
\(\Rightarrow17x=51\)
\(\Rightarrow x=3\)
Vậy \(x=3\)
5)\(3^x+4.3^x=5.3^7\)
\(\Rightarrow3^x\left(1+4\right)=5.3^7\)
\(\Rightarrow5.3^x=5.3^7\)
\(\Rightarrow3^x=3^7\)
\(\Rightarrow x=7\)
Vậy \(x=7\)
6)\(7.2^x-2^x=6.32\)
\(\Rightarrow2^x\left(7-1\right)=6.2^5\)
\(\Rightarrow6.2^x=6.2^5\)
\(\Rightarrow2^x=2^5\)
\(\Rightarrow x=5\)
Vậy \(x=5\)
7)\(15^{3-x}=225\)
\(\Rightarrow15^{3-x}=15^2\)
\(\Rightarrow3-x=2\)
\(\Rightarrow x=1\)
Vậy \(x=1\)
8)\(4.5^x-3=97\)
\(\Rightarrow4.5^x=100\)
\(\Rightarrow5^x=25\)
\(\Rightarrow5^x=5^2\)
\(\Rightarrow x=2\)
Vậy \(x=2\)
9)\(171-3.2^x=123\)
\(\Rightarrow3.2^x=48\)
\(\Rightarrow2^x=16\)
\(\Rightarrow2^x=2^4\)
\(\Rightarrow x=4\)
Vậy \(x=4\)
10)\(180-4.x^5=32\)
\(\Rightarrow4.x^5=148\)
\(\Rightarrow x^5=37\)//Đề có lỗi không ???
a. 22x - 3 = 29
<=> 2x - 3 = 9
<=> x = 6
b.24 - x = 210
<=> 4 - x = 10
<=> x = -6
c. 3x = 19/3
<=> Tự tính
d. 2x - 3 = 2-11
<=> 2x = \(\frac{6145}{2048}\)
<=> Tự tính
Bài làm
a) 0 : x = 0
=> x = 0 : 0 ( vô lí )
Vậy x thuộc tập hợp rỗng.
b) 4x = 64
=> 4x = 43
=> x = 3
Vậy x = 3
c) 2x = 16
=> 2x = 2 4
=> x = 4
Vậy x = 4
d) 9 x - 1 = 9
=> x - 1 = 1
=> x = 2
Vậy x = 2
e) x4 = 16
=> x4 = 24
=> x = 2
Vậy x = 2
g) 2x : 25 = 2
=> 2x - 5 = 21
=> x - 5 = 1
=> x = 6
Vậy x = 6
8x : 2x = 4
<=> (8 : 2)x = 4
<=> 4x = 4
<=> x = 1
S = 22 + 42 + 62 + ... + 202
S = (22 + 42 + 62 + ... + 202)
S =22.(12 + 22 + 32 + ... + 102 )
S = 4. 385 = 1540
/Tìm X biết
\(8^x:2^x=4\)
\(\Leftrightarrow\left(8:2\right)^x=4\)
\(\Rightarrow4^x=4^1\)
\(\Rightarrow x=1\)
a. ( x - 1 )2 = 25
<=> \(\orbr{\begin{cases}x-1=5\\x-1=-5\end{cases}}\)
<=>\(\orbr{\begin{cases}x=6\\x=-4\end{cases}}\)
b. 2x + 2 - 2x = 96
<=> 2x.4-2x=96
<=> 2x.3=96
<=> 2x=32=25
<=> x=5
c. 2x . 7 = 224
<=> 2x=32=25
<=> x=5
d. ( 7x - 11 )3 = 25 . 52 = 200 (xem lại đề)
e. 9 < 3x < 81
<=> 32<3x<34
<=> 2<x<4